Tourist Road Experiences Around Lake Bunyonyi In Kabale, South Western Uganda - Atuheire, Timothy (Kabale University, 2023)
This study investigated "Tourist road experiences around Lake Bunyonyi in Kabale, south Esemganda. It was carried out among tourists at Lake Bunyonyi Camp site, including cottages such as Bunyonyi Safaris Resort, Lake Bunyonyi Eco Resort, Bunyonyi Overland Resort. The study was guided by three objectives namely; identify the most common road challenges faced by tourists around Lake Bunyonyi in Kabale. me perceptions and attitudes of tourists towards road infrastructure in the Lake Bunyonyi area and identify strategies for improving road conditions and infrastructure in the area around Lake Bunyonyi. The study employed qualitative research design and collected data through interviews as instruments for data collection. Both primary and secondary methods of research data collection were used. The study employed both purposive and non-probability sampling design using quota sampling technique and it involved a sample size of 30 respondents. The study found out chat the tourist road experiences are both negative and positive. The study found that the state of the roads in the area is poor, with potholes, no street lighting and also with poor signage. Also the poor conditions of the roads in the area often cause life threatening events such as accidents, and increased safety challenges to the tourists using these roads. A number of strategies have been put in place to improve on road conditions but a lot is still desired. The study further concluded that although the roads are poor, experiences of the tourists vary depending on the effect of what is experienced and the overall impact on tourist satisfaction. The study further brought to the fore some action oriented recommendations towards improvement of road experiences in order to realize tourist satisfaction such as the need for improving the road conditions through constant renovation. However the study highlights that this calls for the attention of government and increased community participation in road maintenance activities if tourist satisfaction is to be boosted in the area. Therefore, Uganda National Roads Authority should focus on developing a comprehensive road infrastructure plan, which includes regular maintenance, repairing of potholes, and improving road signage by installing signposts to provide clear directions to tourists using the roads leading to lake Bunyonyi campsite.